Simulating the influence of the South Atlantic dipole on the South Atlantic convergence zone during neutral ENSO - Bombardi RJ; Carvalho, Leila M. V.; Jones, C. (Springer, 2014)
The South Atlantic Convergence Zone (SACZ) is an intrinsic characteristic of the South American Summer Monsoon. In a recent study, we verified that the main mode of coupled variability over the South Atlantic (South Atlantic Dipole (SAD)) plays a role in modulating the position of extratropical cyclones that affect the SACZ precipitation. In this study, we perform numerical experiments to further investigate the mechanisms between SAD and the SACZ. Numerical experiments forced with prescribed SST anomalies showed that, even though the Atlantic SST affects the position of the cyclone associated with the SACZ, the atmospheric response and precipitation patterns over land are opposed to the observations. On the other hand, experiments forced with prescribed anomalous driving fields showed that the atmospheric component of SAD plays a significant role for the right position and intensity of precipitation associated with the SACZ. SAD negative anomalies provide the low-level and upper-level atmospheric support for the intensification of the cyclone at surface and for the increase in precipitation over the land portion of the SACZ. Therefore, the numerical experiments suggest that, during El Niño Southern Oscillation neutral conditions, the SACZ precipitation variability associated with SAD is largely dependent on the atmospheric variability rather than the underlying SST.